Biomarkers of lymph node metastasis in colorectal cancer: update - Zhu, Xiao; Lin, Shui-quan; Xie, Jun; Wang, Li-hui; Zhang, Li-juan; Xu, Ling-ling; Xu, Jian-guang; Lv, Yang-bo (Frontiers in Oncology, 2024)
Colorectal cancer (CRC) ranks as the second leading cause of cancer-related deaths globally, trailing only behind lung cancer, and stands as the third most prevalent malignant tumor, following lung and breast cancers. The primary cause of mortality in colorectal cancer (CRC) stems from distant metastasis. Among the various routes of metastasis in CRC, lymph node metastasis predominates, serving as a pivotal factor in both prognostication and treatment decisions for patients. This intricate cascade of events involves multifaceted molecular mechanisms, highlighting the complexity underlying lymph node metastasis in CRC. The cytokines or proteins involved in lymph node metastasis may represent the most promising lymph node metastasis markers for clinical use. In this review, we aim to consolidate the current understanding of the mechanisms and pathophysiology underlying lymph node metastasis in colorectal cancer (CRC), drawing upon insights from the most recent literatures. We also provide an overview of the latest advancements in comprehending the molecular underpinnings of lymph node metastasis in CRC, along with the potential of innovative targeted therapies. These advancements hold promise for enhancing the prognosis of CRC patients by addressing the challenges posed by lymph node metastasis.